A Topology-Based Algorithm for Directed Network Alignment - Qingyu Zou; Fu Liu; Tao Hou; Yihan Jiang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Network alignment has brought significant advances to our understanding of complex networks, for example, the Worldwide Web, biological networks, and social networks. Triangles comprised of three nodes are the simplest subnet in the directed network. The distribution of triangles is an important indicator of understanding the dynamics and function of directed networks. In this paper, we present a novel alignment algorithm for directed networks only based on topology structure, which can be used for any two networks. The transcriptional regulatory networks (TRNs) of E. coli and S. cerevisiae are used to evaluate the algorithm. Experimental results demonstrate that the algorithm proposed is efficient for aligning directed networks.DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.2951